Cronotanatognose, utilização da polpa dentária como ferramenta para determinar o tempo de morte: uma revisão (Research, Society and Development, 2021)
The post-mortem interval is the period of time that has passed since the death occurred until the moment when the body and /or human remnants are studied. The estimation of this interval is a matter of great relevance in the forensic sphere due to its important role in the resolution of criminal cases. Teeth are fundamental structures in a forensic context due to their high strength and specificity. Therefore, this article aims to present how the dental pulp is used to determine the time of death of the corpse. A systematic review of the scientific literature was carried out with a descriptive and qualitative character, allowing the inclusion of experimental and non-experimental studies for a complete coverage of the analyzed phenomenon. For data collection, online searches were carried out on the bases: SciElo, LILACS and Elsevier. All journal papers that used the selected terms were included in this review. The degradation of dental pulp after death consists of a complex process that has not been fully studied, but with the techniques and changes shown in the text, reliable post-mortem interval results are possible.